From Concept to Practice: Using the School Health Index to Create Healthy School Environments in Rhode Island Elementary Schools - Deborah N. Pearlman, PhD; Elizabeth Dowling, MPH; Cheryl Bayuk; Kathleen Cullinen, MS, RD; Ann Kelsey Thacher, MS (Centers for Disease Control and Prevention, 2005)
Introduction The prevalence of childhood obesity is increasing, and schools are ideal places to support healthy eating and physical activity. In 2000, the Centers for Disease Control and Prevention (CDC) developed the School Health Index, a self-assessment and planning tool that helps schools evaluate and improve physical activity and nutrition programs and policies. Although many state education agencies, health departments, and individual schools have used the School Health Index, few systematic evaluations of the tool have been performed. We examined the physical activity and nutrition environments in Rhode Island's public elementary schools with high and low minority student enrollments and evaluated a school-based environmental and policy intervention that included implementation of the School Health Index. Methods As part of a CDC Division of Nutrition and Physical Activity cooperative agreement awarded to the Rhode Island Department of Health, we conducted a needs assessment of 102 elementary schools and implemented an intervention in four inner-city elementary schools. In phase 1, we analyzed the Rhode Island Needs Assessment Tool (RINAT), a telephone survey of principals in approximately 50% of all Rhode Island public elementary schools in the state during the 2001-2002 school year (n = 102). Comparisons of the nutrition and physical activity environments of schools with low and high minority enrollment were calculated by cross-tabulation with the chi-square test. In phase 2, we used process and outcome evaluation data to assess the use of the School Health Index in creating healthier environments in schools. Our intervention - Eat Healthy and Get Active! - involved implementing three of the eight School Health Index modules in four Rhode Island elementary schools. Results Survey data revealed that schools with high minority enrollment (student enrollment of ≥10% black, ≥25% Hispanic, or both) offered few programs supporting healthy eating and physical activity (P < .05). Schools with high and low minority enrollment both offered nonnutritious foods and beverages. Process evaluation data revealed that 1) principals play a pivotal role on School Health Index teams, 2) schoolwide validation of a team's small successes is crucial for sustaining a commitment to healthy lifestyle policies and programs, and 3) external facilitators are essential for implementation success. Outcome data showed that all schools developed at least one policy or environmental strategy to create a healthy school environment. Only two schools implemented immediate changes. Conclusion Needs assessment, external facilitation, and evaluation are the foundation for sustainable school-based policies. Although the School Health Index is universally perceived as a user-friendly assessment tool, implementation is likely to be less successful in schools with low staff morale, budgetary constraints, and inconsistent administrator support.